2019
DOI: 10.1021/acs.est.9b03456
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pyrophosphate on the Generation of Soluble Mn(III) from Reactions Involving Mn Oxides and Mn(VII)

Abstract: The detection of soluble Mn­(III) is typically accomplished using strong complexing agents to trap Mn­(III), but the generation of soluble Mn­(III) induced by strong complexing agents has seldom been considered. In this study, pyrophosphate (PP), a nonredox active ligand, was chosen as a typical Mn­(III) chelating reagent to study the influence of ligands on soluble Mn­(III) formation in reactions involving Mn oxides and Mn­(VII). The presence of excess PP induced the generation of soluble Mn­(III)-PP from α- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(38 citation statements)
references
References 56 publications
4
34
0
Order By: Relevance
“…As demonstrated in Figure , no characteristic peaks of MnO 2 were observed after the addition of PP both in KMnO 4 /Na 2 S 2 O 3 and KMnO 4 /NH 2 OH·HCl systems. Instead, obvious peaks of Mn(III)‐PP were detected, indicating the presence of PP induced the generation of Mn(III)‐PP from reactions of KMnO 4 with Na 2 S 2 O 3 , and KMnO 4 with NH 2 OH·HCl, which is in agreement with literature (Liu, Sun, Qiao, & Guan, ). Many studies have shown that Mn(III)‐PP is less redox‐reactive (Nico & Zasoski, , ) and cannot oxidize contaminants effectively.…”
Section: Resultssupporting
confidence: 91%
“…As demonstrated in Figure , no characteristic peaks of MnO 2 were observed after the addition of PP both in KMnO 4 /Na 2 S 2 O 3 and KMnO 4 /NH 2 OH·HCl systems. Instead, obvious peaks of Mn(III)‐PP were detected, indicating the presence of PP induced the generation of Mn(III)‐PP from reactions of KMnO 4 with Na 2 S 2 O 3 , and KMnO 4 with NH 2 OH·HCl, which is in agreement with literature (Liu, Sun, Qiao, & Guan, ). Many studies have shown that Mn(III)‐PP is less redox‐reactive (Nico & Zasoski, , ) and cannot oxidize contaminants effectively.…”
Section: Resultssupporting
confidence: 91%
“…More generally, the presence in the reactive medium of compounds chelating Mn, and more especially Mn(III), is expected to enhance the oxidative process (Ma et al, 2020). With this respect, pyrophosphate (PP) appears especially relevant owing to its strong affinity for Mn(III) (Liu et al, 2019;Marafatto et al, 2018;Parker et al, 2004;Soldatova et al, 2017). The relevance of PP is further increased by its common formation in natural environments, as the simplest polymer of orthophosphate resulting from the breakdown of ATP and ADP (Klewicki and Morgan, 1999b;Trouwborst et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Mn(III) can be formed via the oxidation of Mn(II), 21 the one-electron reduction of Mn(IV), 22 and a conproportionation reaction between Mn(II) and Mn(IV). 23 Mn(III) is found in the minerals bixbyite (Mn 2 O 3 ), feitknechtite, groutite, and manganite (MnO[OH]), the mixed-charge phase hausmannite (Mn 3 O 4 ), and in minerals with more complex chemistries. Free aqueous Mn(III) is prone to disproportionation to yield dissolved Mn(II) and solid Mn(IV) and is assumed to be short-lived in solution, which has led to a general underappreciation of Mn(III) in the traditional paradigm of Mn redox cycling.…”
Section: ■ Introductionmentioning
confidence: 99%
“…39 A molar extinction coefficient of 6750 M −1 cm −1 was used to calculate Mn(III) concentrations. 23 The Mn content of MnO 2 stock solutions was quantified by monitoring the absorbance following the addition of LBB at 623 nm (see the Supporting Information for details). 40 Standard curves were prepared with LBB and KMnO 4 (Figure S2).…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation